Clinical characteristics, risk factors and prognosis of Klebsiella pneumoniae infection in patients with different states of immune function: a retrospective study - Xin Wang; Chonghe Xu; Chao Qin; Juan Liu; Xiaoli Kong; Zhijun Zhu; Chenchen Zhang; Wei Xu; Mei Zhu (Frontiers in Cellular and Infection Microbiology)
BackgroundThe aim of our study was to investigate the epidemiology and risk factors of Klebsiella pneumoniae (KP) infection in immunocompromised patients and to compare the differences in prognosis among patients with different immune states in the extended-spectrum beta-lactamase KP (ESBL-KP), the carbapenem-resistant KP (CRKP), and the non-multidrug-resistant KP (non-MDR-KP) groups.MethodsWe conducted a retrospective study in immunocompromised and immunocompetent patients with KP infections who were admitted to Chaohu Hospital of Anhui Medical University from January 2023 to December 2023. We compared demographics, clinical characteristics, treatments, and outcomes across these groups and examined the impact of ESBL-KP, CRKP and non-MDR-KP on cumulative survival rates in populations with different immune states by plotting Kaplan-Meier curves.ResultsOur study included 228 immunocompromised patients and 200 immunocompetent patients. Compared to the immunocompetent group, immunocompromised patients were more likely to have a history of surgery and to use hormone frequently. They tended to rely more on medical devices, including urinary catheters, nasogastric catheters, arterial catheters, venous catheters, mechanical ventilation and endoscopy. Immunocompromised patients had a poorer recovery and were rehospitalized more often than those in immunocompetent patients. In the multivariable analysis, age-adjusted Charlson comorbidity index (aCCI) (OR: 1.292, 95%CI: 1.086-1.537, P < 0.004) and microbiological clearance failure (OR: 4.175, 95%CI: 1.966-8.866, P < 0.001) were the most important risk factors for mortality in immunocompromised patients infected with KP. It was further observed that immunocompromised patients in the ESBL-KP group had the lowest cumulative survival. In contrast, among both all participants and immunocompetent patients, the CRKP group had the lowest cumulative survival, followed by the ESBL-KP group.ConclusionThe clinical characteristics, treatment process and prognosis in immunocompromised patients with KP infections are significantly different from those in immunocompetent patients. In clinical settings, the standardization of invasive procedures and the rational use of antibiotics represent the most effective strategies for preventing and treating KP infection.